The Role of Medicinal Chemistry in the Discovery of Novel Antiviral Agents - Malallah Saeed, Aya Mahmoud; Ahmed ghazal, Haya durgham; Reja, Nawal Ali; Al_Amer Jasim, Fatima Falah abd; Hussein Abd, Ali Mohammed (American Journal of Biomedicine and Pharmacy, 2025)
Antiviral agents have a unique role in the treatment of infectious diseases and represent a substantial portion of the drug marketplace because of the number of viral infections, the lack of successful vaccines, and the inadequacy of other therapeutic modalities to combat viral infections. Medicinal chemistry reveals a vital role in the modernization and productiveness of this drug development process. Antiviral agents predominantly become the drug of choice for a variety of viral infections, mainly HIV, and influenza, accounting for billions of dollars in revenue. The medicinal chemists have done remarkable work in the design and optimization of diverse chemistry libraries through the various methodologies employed for the identification of small molecules preclinically active in vitro against a variety of viruses. Numerous compounds, consisting of various levels of diversity and primarily aromatic rings, were prepared and evaluated in antiviral biochemical and cellular auxiliary screens. Viruses result in a variety of human and animal diseases and are generally not treatable by antibiotics. Although a few spectrum antivirals exist, most are narrow spectrum, and resistance to current drugs is a growing problem. The consistent effort to improve chemical therapies has paved the path for medicinally designed antivirals that targets various stages in the viral lifecycle, and a large number of them are rapidly synthesized and genuine in series. The present medication with respect to the design and discovery of antiviral agents, emphasizing the prevailing methodologies and strategies of medicinal chemistry research that have been furnished to enhance the antiviral therapeutic toolbox. Though the prior medication reveals the key role of medicinal chemistry in the design and discovery of antiviral agents from different aspects, considerable challenges persist to disturb the current antiviral research and development. Further advance in a variety of aspects ranging from cooperative approaches to advancements in methodology and technology continue to fuel inclusive discovery and progress in this area.